Research trends in artificial intelligence chatbots for oral health education and consultation: a narrative review - Su-Yeon Hwang (Journal of Korean Society of Dental Hygiene, 2026)
Objectives: This narrative review examined research trends in artificial intelligence (AI) chatbots for oral health education and counseling, with a particular focus on differences between Korean and international studies in their progress toward clinical application. Methods: International studies were searched in PubMed and Web of Science, and Korean studies in RISS, KCI, and DBpia, with the search limited to publications from 2019 onward. Of the 63 eligible international studies, 12 were purposively sampled to balance dental subspecialty and country of origin, with all studies reporting user or clinical outcomes retained; both Korean studies meeting the criteria were included. The 14 studies were categorized into three translational stages: development, performance evaluation, and effectiveness validation. Results: International studies spanned all three stages and included randomized controlled trials that assessed clinical and behavioral outcomes in patients. In contrast, the Korean studies remained at the development stage, with no assessment of response quality and no effectiveness validation involving actual users. However, many international studies were also preliminary or small in scale, indicating that widespread clinical adoption has not yet been achieved. Conclusions: A pronounced gap exists between Korean and international research in the clinical translation of AI chatbots for oral health education and counseling. To bridge this gap, Korean research should move beyond development toward user-centered evaluation and effectiveness validation, supported by the construction of Korean-language datasets, standardized assessment metrics, and multidisciplinary collaboration involving dental hygienists.